Human Cerebral Cortex Proteome of Fragile X-Associated Tremor/Ataxia Syndrome - Holm, Katharine Nichole; Herren, Anthony W.; Taylor, Sandra L.; Randol, Jamie L.; Kim, Kyoungmi; Espinal, Glenda; Martínez-Cerdeño, Verónica; Pessah, Isaac N.; Hagerman, Randi J.; Hagerman, Paul J. (Frontiers in Molecular Biosciences, 2021)
Fragile X-associated tremor/ataxia syndrome (FXTAS) is an adult-onset neurodegenerative disorder associated with premutation CGG-repeat expansions (55-200 repeats) in the 5’ non-coding portion of the FMR1 gene. Core features of FXTAS include progressive tremor/ataxia, cognitive decline, variable brain volume loss, and white matter disease. The principal histopathological feature of FXTAS is the presence of CNS and non-CNS intranuclear inclusions. To further elucidate the molecular underpinnings of FXTAS through the proteomic characterization of human FXTAS cortexes. Proteomic analysis of FXTAS brain cortical tissue (n=8) identified minor differences in protein abundance compared to age-matched control brains (n=6). Significant differences generally involved decreased abundance, with greatest decreases observed for TNC, CD38, and PSAT1; proteins typically increased in other neurodegenerative diseases. Proteins with the greatest increased abundance include potentially novel neurodegeneration-related proteins, SUMO1/2 and DEK. Proteins with increased abundance had previously been observed to be concentrated in nuclei, suggesting protein aggregation and increased intranuclear activity of these proteins in end-stage FXTAS pathophysiology. The peptide, FMRPolyG, proposed in models of FXTAS pathogenesis but identified in only trace amounts in the earlier study of FXTAS inclusions (Ma et al., 2019), was not identified in any of the FXTAS or control brains in the current study, calling into question the involvement of this peptide in FXTAS pathogenesis. A novel proteomic response to FXTAS disease progression suggests altered RNA binding as well as loss of cell-cell adhesion/structural integrity. Unlike other neurodegenerative diseases, the proteome of end-stage FXTAS does not suggest a strong inflammation-mediated degenerative response.